2011
DOI: 10.1103/physreve.83.017101
|View full text |Cite
|
Sign up to set email alerts
|

Universal patterns in sound amplitudes of songs and music genres

Abstract: We report a statistical analysis over more than eight thousand songs. Specifically, we investigate the probability distribution of the normalized sound amplitudes. Our findings seems to suggest a universal form of distribution which presents a good agreement with a one-parameter stretched Gaussian. We also argue that this parameter can give information on music complexity, and consequently it goes towards classifying songs as well as music genres. Additionally, we present statistical evidences that correlation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Fractal structures were also reported by Hsü and Hsü [21,22] when studying classical pieces concerning frequency intervals. It was also found that the distribution of sound amplitudes may be adjusted by a one-parameter stretched Gaussian and that this non-Gaussian feature is related to correlation aspects present in the songs [23].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Fractal structures were also reported by Hsü and Hsü [21,22] when studying classical pieces concerning frequency intervals. It was also found that the distribution of sound amplitudes may be adjusted by a one-parameter stretched Gaussian and that this non-Gaussian feature is related to correlation aspects present in the songs [23].…”
Section: Introductionmentioning
confidence: 94%
“…Notice that both series, amplitude and intensity, lead to similar behavior, contrarily to what happens with other quantifiers. For instance, when dealing with Hurst exponent is preferable to work with the intensities[23] or volatilities[24], since the amplitudes are intrinsically anti-correlated due the oscillatory nature of the sound. Moreover, we have found that there is a large range of H s and C js possible values.…”
mentioning
confidence: 99%
“…In several contexts, longrange correlations emerge in coupled-like manner with non-Gaussian distributions (see Ref. [28] for a specific example) and here the same happens. Furthermore, if we shuffle the lightning rates among the cities, besides destroying the spatial correlations this process drastically changes the profile of the residual distributions.…”
mentioning
confidence: 87%
“…• taking into account all data points, y = 0.255 + 0.33x, with R 2 = 0.349, 2 Interesting comments on outliers can be found in [33,34] • without the (DG), (AP) and (MM) points, y = 2.964 + 0.164x, with R 2 = 0.769,…”
Section: Outliersmentioning
confidence: 99%